Semiotic Analysis Of The Lyrics Of The Song "Kupu-Kupu Malam" The Work Of Titiek Puspa: Ferdinand De Saussure's Theory - Meiyanti Nurchaerani; Henry; Andy Halim; Alfian; Ario Pamungkas; Syahiid Hidayatullah Rizkyka Hartadhi (Journey: Journal of English Language and Pedagogy, 2025)
This study examines the lyrics of the song "Kupu-Kupu Malam" by Titiek Puspa through the lens of Ferdinand de Saussure's semiotic theory. By analyzing the song’s lyrics as a system of signs composed of signifiers and signifieds, the research explores how meaning is constructed and how the song reflects the social realities of marginalized women, particularly those engaged in nighttime professions. Data was collected through textual transcription and close reading of the song lyrics.Through qualitative descriptive analysis, the study interprets symbolic elements such as "night butterfly," "smiling through tears," and "black blood" to uncover themes of gender inequality, societal judgment, and emotional duality. The analysis further incorporates paradigmatic and syntagmatic relationships within the lyrics to understand how their structure contributes to broader socio-cultural critiques. The findings reveal that "Kupu-Kupu Malam" not only portrays the complex lives of women stigmatized by society but also serves as a poignant commentary on the tension between personal identity and restrictive social norms. This study demonstrates the relevance of semiotic analysis in uncovering the layered meanings embedded in cultural texts, emphasizing empathy and critical reflection toward social issues that persist in both past and present contexts.